Probabilistic time variant assessment of thin-walled steel members under atmospheric corrosion attack - Cascini, Lucrezia; Portioli, Francesco; Landolfo, Raffaele (Journal of Civil Engineering and Management, 2014)
Atmospheric corrosion is a relevant problem for steel structures and components exposed in aggressive environment in case of poor and/or unfeasible maintenance and inspection during service life. As for thin-walled members, the corrosion hazard can be exacerbated due to the thin thickness of components and the coupled effect between corrosion and buckling can significantly reduce the structural capacity of such structures. Following these considerations, this paper presents a study on the reliability of a thin-walled steel section subjected to the damage induced by atmospheric corrosion in outdoor environments, combining predictive corrosion models for metals with structural reliability applications. A general procedure for the evaluation of the time variant capacity is proposed and discussed in detail. Finally, an application to a C-lipped cold formed section is presented and a reliability analysis of the deteriorating section is carried out to evaluate the coupled effect of corrosion and buckling, according to the proposed procedure.